2020
DOI: 10.3389/fcimb.2020.514943
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Salivary Microbial Alteration of Men With Head and Neck Cancer and Its Relationship With Symptoms in Southwest China

Abstract: This study explored the association between oral microbes and head and neck cancer (HNC) as well as symptoms related to patients with HNC before surgical treatment. Fiftysix patients with HNC and 64 matched healthy controls were recruited from West China hospital in Southwest China. The demographic, clinical, and symptom data were collected. Salivary samples were collected to determine the microbial characteristics using 16S rRNA gene sequencing. Patients with HNC presented increased Capnocytophaga abundances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…The samples were obtained from patients with HNSCC, of which OSCC was the most frequently studied tumor [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. The studies also included samples from the following: oropharyngeal squamous cell carcinoma (OPSCC) [ 21 , 43 ], gingival squamous cell carcinoma (GSCC) [ 44 ]; unspecified oral cavity cancer (OCC) (45); oropharyngeal cancers (OPC) [ 45 ]; nasopharyngeal carcinoma (NPC) [ 46 ]; unspecified HNSCCs [ 47 , 48 , 49 , 50 , 51 ]. In addition, certain oral potentially malignant disorders (OPMDs), such as oral leukoplakia, were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were obtained from patients with HNSCC, of which OSCC was the most frequently studied tumor [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. The studies also included samples from the following: oropharyngeal squamous cell carcinoma (OPSCC) [ 21 , 43 ], gingival squamous cell carcinoma (GSCC) [ 44 ]; unspecified oral cavity cancer (OCC) (45); oropharyngeal cancers (OPC) [ 45 ]; nasopharyngeal carcinoma (NPC) [ 46 ]; unspecified HNSCCs [ 47 , 48 , 49 , 50 , 51 ]. In addition, certain oral potentially malignant disorders (OPMDs), such as oral leukoplakia, were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh faeces samples are placed in insulating polystyrene foam containers on an ice bath, transported from the hospital to the laboratory and stored at −80°C. The samples are collected and transported using the adopted method 33…”
Section: Methods and Analysesmentioning
confidence: 99%
“…A 16S rRNA gene sequencing study on Caucasian participants found that a panel of Capnocytophaga, Corynebacterium, Porphyromonas, Haemophilus, Oribacterium, Rothia, and Paludibacter could discriminate between patients with oropharyngeal cancers and oral cavity cancers from age-matched controls (p<0.05) ( 114 ). A recent study demonstrated that an elevated presence of Capnocytophaga (AUC= 0.81 p<0.05) in saliva could be used as a probable screening tool for prognosis and diagnosis of HNC patients ( 115 ). Similarly, abundance of Dialister (p<0.05) in HNC patients correlated with aggressive laryngeal and oral tumors ( 116 ).…”
Section: Salivary Microbiomementioning
confidence: 99%